2017
DOI: 10.1007/s13402-017-0365-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of β-catenin in cisplatin resistance, relapse and prognosis of head and neck squamous cell carcinoma

Abstract: From our results we conclude that β-catenin may contribute to HNSCC therapy resistance and disease relapse. As such, β-catenin may be explored as a therapeutic target along with conventional therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…The cell viability of parental SCC‐131 cells, p38‐inhibited SCC‐131 cells, parental Cal27 cells, and p38‐inhibited Cal27 cells after cisplatin treatment was assessed by MTT assay as reported earlier …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell viability of parental SCC‐131 cells, p38‐inhibited SCC‐131 cells, parental Cal27 cells, and p38‐inhibited Cal27 cells after cisplatin treatment was assessed by MTT assay as reported earlier …”
Section: Methodsmentioning
confidence: 99%
“…Colony forming capacity of parental SCC‐131 cells, p38‐inhibited SCC‐131 cells, parental Cal27 cells and p38‐inhibited Cal27 was performed by clonogenic assay as previously reported …”
Section: Methodsmentioning
confidence: 99%
“…It has been confirmed that the reduction in membranous β-catenin was associated with invasive growth, higher risk of lymph node metastasis and shorter survival [13,34,46,47]. The higher level of cytoplasmic/nuclear β-catenin delocalization detected in the surgical margin correlated with higher recurrence rate [48]. Depending on the study, the nuclear expression of β-catenin was observed in 23% of pharyngeal tumors [49], 43% of laryngeal tumors [40], 33% of tongue carcinomas [50], 78% of tongue carcinomas [51] and 17% of HPV-negative oropharyngeal carcinomas [52].…”
Section: Introductionmentioning
confidence: 83%
“…This was mediated by the activation of the Wnt pathway [133]. In the same manner, the induction of Wnt signaling by the inhibition of GSK-3β using lithium chloride led to enhanced DNA repair, evasion of apoptosis and cisplatin resistance [48]. The acquired cisplatin resistance in tongue cancer cells was associated with the induction of WNT-2B and GLUT1 overexpression, and the knockdown of WNT-2B sensitized resistant cells to cisplatin treatment and reduced colony formation in vitro and tumor growth in vivo [134].…”
Section: Functional Significance Of Wnt/β-catenin Pathway Dysregulationmentioning
confidence: 91%
See 1 more Smart Citation